A=9/4(h-53

Simple and best practice solution for A=9/4(h-53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A=9/4(h-53 equation:



=9/4(A-53
We move all terms to the left:
-(9/4(A-53)=0
Domain of the equation: 4(A-53)!=0
A∈R
We multiply all the terms by the denominator
-(9=0
We add all the numbers together, and all the variables
=0
A=0/1
A=0

See similar equations:

| 3(5x+6)=2x-9 | | 2x+12+x=-12 | | -18=-16+b | | 8x-(3x+318)=287 | | 0.05x+5=0.25 | | 25+4t=97 | | 12x-6=9x+1+3x | | r/4=2.53 | | 4u+8=80 | | 85+5+9x=180 | | 4(-10b-2)=-128 | | 4x-1+7x=11x-1 | | 2(1-x)-(1-4x)=7 | | 8x–(3x+318)=287 | | -8(-7x+5=8(7x-5) | | 3x+32=13x+22 | | 6(n+4)-2n=32 | | 6-5x-14=-8x+9-2 | | 6x-2x-4=2(2x-7) | | -2(x^2-3)=x^2-42 | | 7(6k+2)=308 | | 4w-10=5+2w | | X-1=-2x-7 | | 7t+9=2 | | 6x-2x-4=2(2x-7 | | 6x-2x+4=18 | | 7t=29 | | 6y+33=99 | | 3a+1=-a+3 | | 28x+66=33 | | -(7+3x)=-4(x+4)-1 | | 89=5(5+4k)-4k |

Equations solver categories